Analysis of Japan's Dual Influence on Southeast Asian Infrastructure Diplomacy - Wei, Dehua; Tang, Zhanfeng (International Journal of Global Economics and Management, 2024)
This paper examines the dual influence of Japan and China in infrastructure diplomacy in Southeast Asia since 2015. The competition between the two countries in infrastructure diplomacy in Southeast Asia is mainly manifested in investment and financing modes and high-speed rail projects, aiming at promoting their domestic economies and expanding geopolitical influence. This competition has brought economic dividends to Southeast Asian countries, but it has also increased the pressure on these countries to "choose sides station", which has led to an increase in internal tensions within the region. Although Sino- Japanese confrontation has weakened bilateral relations, there is the possibility of cooperation in promoting connectivity in Southeast Asia, and the two sides share common interests in this regard. Competition between China and Japan in high-speed rail and other projects provides more choices for Southeast Asian countries, which complicates the development of infrastructure and affecting regional stability.